Sleep behaviors modify the association between hemoglobin concentration and respiratory infection: a prospective cohort analysis - Zhu, Yongkui; Chen, Qian; Wang, Mengying; Qian, Huan; Song, Qiying; Liu, Bofei (Frontiers in Physiology, 2025)
InterpretationHb and respiratory infection showed a nonlinear U-shaped association; such a relation is modified by the chronotype sleep behavior.ObjectiveTo examine the association between Hb and the incidence of hospitalized respiratory infection, and to explore potential modification effects of sleep behaviors.MethodsIncluded were 292,568 individuals without respiratory disease, cancer, or anemia diagnosis in the United Kingdom Biobank . Hb (g/dL) was measured at baseline. The interaction between Hb and sleep behaviors, including sleep duration, insomnia, chronotype, and daytime sleepiness with respiratory infection, was tested.ResultsThe cohort was followed up at a median 12.6 years, and 16,669 incident respiratory infections (9,334 in men, 7,335 in women) were identified. There was a nonlinear U-shaped association between Hb and respiratory infection in both men and women, where the risk increased markedly with Hb above 15.0 g/dL for men and 13.5 g/dL for women. In men, compared with the third quintile group, the hazard ratio (HR; 95% confidence interval [CI]) of respiratory infection in the Q1, Q2, Q4, and Q5 quintile groups was 1.28 (1.21–1.37), 1.07 (1.00–1.14), 1.06 (0.99–1.13), and 1.09 (1.02–1.17), respectively. In women, the HR (95% CI) was 1.20 (1.12–1.29), 1.09 (1.01–1.17), 1.01 (0.94–1.09), and 1.05 (0.98–1.13) in the Q1, Q2, Q4, and Q5 quintile groups of Hb, respectively, compared with the third quintile group. There was a significant interaction between Hb concentration and chronotype on the risk of respiratory infection (P for interaction = 0.005). The elevated risk of respiratory infection associated with Hb was more pronounced among participants with late chronotype.ConclusionThe study suggests that Hb and respiratory infection have a nonlinear U-shaped association and that such a relation is modified by chronotype.